Dear white people [videorecording (DVD)] - Simien, Justin; Williams, Tyler James, 1992-; Thompson, Tessa, 1983-; Parris, Teyonah ([Publisher not identified], 2015)
A sharp and funny comedy about a group of African-American students as they navigate campus life and racial boundaries at a predominately white college. A sly, provocative satire about being a black face in a white place.